Effect of Center-Pivot Irrigation Intensity on Groundwater Level Dynamics in the Agro-Pastoral Ecotone of Northern China - Lian, Jie; Li, Yulin; Li, Yuqiang; Zhao, Xueyong; Zhang, Tonghui; Wang, Xinyuan; Wang, Xuyang; Wang, Lilong; Zhang, Rui (Frontiers in Environmental Science, 2022)
Groundwater-based irrigation is an effective buffer against continuous drought in arid and semi-arid regions with intensive agriculture. However, aquifer depletion inevitably results from long-term unplanned irrigation. This depletion depends on well density (a proxy for pumping capacity), but density statistics are poorly recorded and rarely assessed. The lack of this data is a critical barrier to scheduling irrigation and sustainably managing groundwater in regions such as Northern China’s agro-pastoral ecotone. In the present study, we examined a typical area with center-pivot irrigation (CPI) to locate irrigation wells in time series Landsat images and pixels of the normalized-difference vegetation index (NDVI). We monitored groundwater levels (GL) from 2019 to 2020. Kernel density estimates showed sharply accelerated land use transformation to groundwater-fed irrigation, and statistically significant increases of the mean NDVI of CPI pixels (by 30.6 to 59.2%) after transformation from natural grassland to irrigated pasture. The deeper GL (> 20 m) fell much faster (0.94 ± 0.05 m yr-1) than the shallower GL (< 10 m, 0.63 ± 0.06 m yr-1) and medium GL (10 to 20 m, 0.72 ± 0.3 m yr-1) during the study period. The kernel density was strongly correlated with the change in GL (0.935, p <0.01). Our results demonstrate that GL will fall faster with increasing irrigation well density, particularly in areas with a deep-water table. To mitigate groundwater depletion, it’s necessary to increase the space between center-pivot irrigation systems in areas with dense irrigation, and implement measures to balance water use with recharge rates for sustainable groundwater management.